Immigration Trauma among Hispanic Youth: Missed by Trauma Assessments and Predictive of Depression and PTSD Symptoms - de Arellano, Michael A. (J Lat Psychol, 2017)
Few quantitative studies have examined the rate of exposure to traumatic events during immigration among Hispanics or its relation to mental health outcomes. Failing to capture traumatic events that occur during immigration may impede investigations of trauma and related mental health disparities with Hispanics. In order to better understand the need for immigration-related trauma assessment, interviews were conducted with 131 immigrant Hispanic youth. First, youth completed a comprehensive trauma assessment interview. Items were added to the interview to assess if each traumatic event occurred during the process of immigration. An immigration-focused module was then added to the end of the assessment. A substantial minority of youths reported experiencing a traumatic event during immigration (n = 39; 29.8%). The majority of these were not captured by the standard trauma assessment (n = 32; 82.1% of those with in-transit trauma). Of these, the majority stated that the process of immigration itself was traumatic, but had not indicated experiencing any event assessed during the standard trauma assessment (n = 28; 87.5% of those with unidentified in-transit trauma). The traumatic events that were not captured during the standard trauma assessment significantly predicted both depression (p < .001) and PTSD symptoms (p = .012). Results suggest that standard trauma assessments may not capture traumatic events that occur during immigration for Hispanic youth. Failing to capture these events during trauma assessment may have large implications for research on trauma-related mental health disparities, as the events that were not captured overlapped significantly with depression and PTSD.